UJI TOKSISITAS EKSTRAK KULIT BATANG RENGAS (Gluta renghas) TERHADAP LARVA UDANG Artemia salina UNTUK PENGEMBANGAN MODUL PEMBELAJARAN PADA KONSEP KESEIMBANGAN LINGKUNGAN KELAS X SMA - Budi Syahputra Rio; Nursal '; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted ontoxicity tests of rengas (Glutarenghas) bark extract to shrimp larvae Artemia salina for the developing of learningmodules on the concept of environmental balance class X Senior High School in July toSeptember 2015. This research aims to determine the toxicity of rengas (Gluta renghas)bark extract to shrimp larvae of Artemia salina and produce learning modules on theconcept of environmental balance of class X Senior High School. This research wascarried out by two stages. The first stage is an experimental research using BrineShrimp Lethality Test (BSLT) method which consisted of 5 treatments and 3replications. Parameters measured were the mortality of shrimp larvae Artemia salina.The data obtained and analyzed by probit analysis using regression equation. Thesecond stage is the development of research learning modules using ADDIEdevelopment model (Analyze, Design, Development, Implementation and Evaluation)conducted into 3 stages: Analyze, Design and Development. The research of dataobtained from the development of the learning modules are validated by the validationsheet 3 validator by using 5 criteria of validity and analyzed descriptively. The resultsshowed that the extract of bark rengas (Gluta renghas) is toxic to shrimp larvae ofArtemia salina. It can be seen from the LC50 values of 599.79 ppm, while the results ofresearch on the development of learning modules that are already well developed andcan be used or tested in a study at the school on the concept of environmental balanceof class X Senior High School with a mean result of learning modules by thirdassessment validator is valid with an average assessment is 3.79.Key Words: Toxicity Test, Rengas (Gluta renghas), Artemia salina, Learning Modules